2013
DOI: 10.1017/s1368980013001328
|View full text |Cite
|
Sign up to set email alerts
|

Non-Western immigrant children have lower 25-hydroxyvitamin D than children from Western families

Abstract: Objective: To determine if children aged 1-6 years from non-Western immigrant families have lower serum 25-hydroxyvitamin D (25(OH)D) levels than children from Western-born families and examine which factors influence this relationship. Design: Cross-sectional study. Setting: Toronto, Canada. Subjects: Healthy children (n 1540) recruited through the TARGet Kids! practicebased research network. Serum 25(OH)D concentrations of non-Western immigrants were compared with those of children from Western-born families… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…Other Canadian research has also reported that seemingly healthy nonwestern immigrant children are at higher risk of having deficient-insufficient vitamin D status (12%) compared with western-born children (5%) (Omand et al 2014). However, after cow's milk intake, vitamin D supplementation, season, and age were taken into account, this relationship was no longer significant, so the relationship between immigration status and vitamin D status may be mediated by these variables.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Other Canadian research has also reported that seemingly healthy nonwestern immigrant children are at higher risk of having deficient-insufficient vitamin D status (12%) compared with western-born children (5%) (Omand et al 2014). However, after cow's milk intake, vitamin D supplementation, season, and age were taken into account, this relationship was no longer significant, so the relationship between immigration status and vitamin D status may be mediated by these variables.…”
Section: Discussionmentioning
confidence: 91%
“…Healthy immigrant children may also be at risk for vitamin D deficiency as a Toronto-based study reported that nonwestern immigrant children have a 1.9 times higher risk of having low vitamin D status below 50 nmol/L (12%) than western-born children (5%) (Omand et al 2014). However, once the analysis was adjusted for cow's milk intake, vitamin D supplementation, season, and age, the relationship was no longer significant, meaning these variables may mediate vitamin D status among immigrant children.…”
Section: Introductionmentioning
confidence: 99%
“…African, Middle Eastern, South Asian), who are already at high risk of vitamin D deficiency due to skin pigmentation, clothing style, sun avoidance behaviour and genetics. These groups are known to be at higher risk of 25(OH)D deficiency in HLC compared to native populations [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Higher risk of femoral neck osteoporosis among post-menopausal females of South Asian ancestry has been noted in the United States [11], underscoring the need for close monitoring. Comprehensive data are lacking for the Canadian population, except for a small study of South Asian and East Asian students from the University of Toronto [12] and a study of Non-Western immigrant children between the ages of 1–6 living in Toronto [13].…”
Section: Introductionmentioning
confidence: 99%